Religious Dialogic: A Critical Evaluation of Wole Soyinka’s The Trial of Brother Jero and Femi Osofisan’s Midnight Hotel - Dawodu, Sunday Olaoluwagbamila (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
Wole Soyinka and Femi Osofisan are two writers known for the employment of satire as commentaries on the socio-political landscape of Africa. Their works, The Trial of Brother Jero and Midnight Hotels therefore provide ideas for a discourse on religion and its implication for contemporary post-colonial Africa societies in general and Nigeria in particular. Specifically, this paper discusses the nature of religion within these two plays. Noticeably, the plays are set against the same background, Lagos, Nigeria, a microcosm of a cosmopolitan society. In doing this, I focus on the examination of the different characters and characterization in the plays, using them as metaphors for the understanding and the perception of general attitudes towards religious discourse: fanaticism, religion manipulation, insensitivity, conspiracy, religion conunercialization, and other social vices in relation to the notions and practice of religion in any multi-religious contemporary society.